The Rosie result - Simsion, Graeme C (Don Tillman series, 2019)
Don Tillman and Rosie Jarman are back in Australia after a decade in New York, and they're about to face their most important challenge. Their son, Hudson, is struggling at school: he's socially awkward and not fitting in. Don's spent a lifetime trying to fit in, so who better to teach Hudson the skills he needs? The Hudson Project will require the help of friends old and new, force Don to decide how much to guide Hudson and how much to let him be himself, and raise some significant questions about his own identity. Meanwhile, there are multiple distractions to deal with: the Genetics Lecture Outrage, Rosie's troubles at work, estrangement from his best friend Gene ... And opening a cocktail bar.